LEGAL ACTION ON NIGERIAN WHO EXTENDS LIMIT OF IMMIGRATION RESIDENCE PERMIT: CASE STUDIES IN IMMIGRATION OFFICE OF WEST JAKARTA - M. Alvi Syahrin; Anindito Rizki Wiraputra; Dwi Septianto (Polteknik Imigrasi, 2018)
The increasing migration of Nigerian citizens in Indonesia has a mixed impact. Not only the economic sector, but also the increasing number of violations and immigration crimes. The Immigration Office of West Jakarta, which is the jurisdiction of the distribution of Nigerian residences, faces quite difficult problems. The formulation of the problems to be examined in this paper are as follows: (1) How do immigration actions carried out by Immigration Office of West Jakarta in resolving cases of Nigerian citizens who exceed the immigration residence permit time limit and (2) What are the obstacles faced by Immigration Office of West Jakarta in resolving the case. The research method used is qualitative empirical legal research. Based on the results of the discussion, the following legal facts are obtained. The efforts made by Immigration Office of West Jakarta in overcoming abuse of immigration permits by Nigerian citizens are divided into 2 (two) parts, namely preventive efforts and repressive efforts. Preventive efforts carried out by the Immigration Office of West Jakarta are well underway and in accordance with existing regulations. The preventive efforts are realized in 2 (two) systems, namely administrative supervision and field supervision. In addition, these preventive efforts have proven effective with quite a number of Nigerians who abuse immigration permits by the Immigration Office of West Jakarta. Then the existing repressions are felt to require changes in the granting of actions / punishments against Nigerian people who abuse immigration permits. The change is in the form of providing legal action for investigating the violators to take precedence. Because all this time what happened in the field of giving immigration action was prioritized in giving action to Nigerian people who misused immigration permits. Even though the provision of immigration actions does not give a deterrent effect to these actors. So that the impact of these actors will do the same thing again. In practice, in the field of supervision and repression of Nigerian citizens who abuse immigration residence permits carried out by the Immigration Office of West Jakarta, there must be various problems. These problems are divided into 2 (two) factors, namely from the outside and from within. The external factor itself consists of the motives of some Nigerian citizens who came to Indonesia. Then there is a fictitious sponsor that increasingly makes it difficult to trace the perpetrators of abuse of immigration permits. Furthermore, the imbalance between the area of ​​West Jakarta's work area and the number of personnel and equipment that does not support this. Then from the point of view of internal factors which are the obstacles is the lack of supporting factors in carrying out supervision and repression of Nigerian citizens who abuse immigration permits. Finally, the attitude of the immigration officers was less assertive in giving action to Nigerian citizens who committed abuse of immigration permits.